Peanut skins as a natural antimicrobial feed additive to reduce the transmission of salmonella in poultry meat produced for human consumption - Redhead, Adam K.; Noor Azman, Nur Fatin Inazlina; Nasaruddin, Anis Izzaty; Vu, Thien; Santos, Fernanda; Malheiros, Ramon; Hussin, Anis Shobirin Meor; Toomer, Ondulla T. (International Association for Food Protection, 2021)
Salmonella is the leading cause of bacterial foodborne zoonoses in humans. Thus, the development of strategies to control bacterial pathogens in poultry is essential. Peanut skins, a considerable waste by-product of the peanut industry is discarded and of little economic value. However, peanut skins contain identified polyphenolic compounds that have antimicrobial properties. Hence, we aim to investigate the use of peanut skins as an antibacterial feed additive in the diets of broilers to prevent the proliferation of Salmonella Enteritidis (SE). One hundred sixty male hatchlings (Ross 308) were randomly assigned to (i) peanut skin diet without SE inoculation (PS); (ii) peanut skin diet and SE inoculation (PSSE); (iii) control diet without SE inoculation (CON); and (iv) control diet with SE inoculation (CONSE). Feed intake and body weights were determined at weeks 0 and 5. On days 10 and 24 posthatch, three birds per pen (24 total) from each treatment group were euthanized, and the liver, spleen, small intestine, and ceca were collected. The weights of the liver, spleen, and ceca were recorded. Organ invasion was determined by counting SE colonies. Each pen served as an experimental unit and was analyzed by using a t test. Performance data were analyzed in a completely randomized design by using a general linear mixed model to evaluate differences. There were no significant differences (P > 0.05) in weekly average pen body weight, total feed consumption, bird weight gain, and feed conversion ratio between the treatment groups. There were no significant differences in SE CFU per gram for fecal, litter, or feed between the treatment groups CONSE and PSSE. However, for both fecal and litter, the PSSE treatment group tended (P ≤ 0.1) to have a lower Salmonella CFU per gram compared with the CONSE treatment group. The results indicate that peanut skins may have potential application as an antimicrobial feed additive to reduce the transmission or proliferation of SE in poultry environments or flocks.